Kiai’s Transformational Leadership in Policy Making for Realizing the Quality of Islamic Boarding Schools - Khoiri, Naillul; Patoni, Achmad; Tanzeh, Ahmad (Technium Social Sciences Journal, 2022)
This research is motivated by the theory of transformational leadership in the style of the Prophet Muhammad, which is commonly referred to as prophetic transformational leadership. As it is known that the phenomenon of kiai leadership in the eyes of the people is unique. The existence of a kiai figure as a leader is not just a figure who has a position as a leader in an organization as leaders in general. More than that, kiai is the image of a figure who has an image that is identical to the image of prophethood (al ulama warasatul anbiya). The existence of kiai leadership is also perceived by his followers as an image of leadership that is identical to the leadership style of the prophets. A person’s success in becoming a leader is determined by the quality of certain traits or characters that exist in the leader. These characters are related to physical, mental, psychological, personality, and intellectual. The approach in this study uses a qualitative approach with the type of research being a multi-site study. Data collection techniques using in-depth interviews, participant observation, and documentation. Data were analyzed repeatedly through single data analysis and cross-site analysis. The findings of this study are a) a charismatic and revolutionary leadership model approach; b) policies based on the mandate of the institution’s vision, mission, and goals, as well as mandates c) high commitment to the quality of Islamic boarding school values taught by muassis with policies on recruitment of educators and alumni-based education; d) policy making is more based on the basis by always avoiding personal policy making.